Design and manufacture of consumer complaint information systems at PT. Sahabat Waskita Teknik Web-based - Silvia Sihombing, Emma; Sharyanto, Sharyanto; Ulan Bani, Alexius (Journal of Engineering, Technology and Computing (JETCom), 2024)
PT Sahabat Waskita Teknik is a company that trades several heavy equipment for construction, industrial pumps and accessories located in the Central Jakarta area. This research aims to overcome the problem of managing consumer complaints that are currently manual and prone to human error. Therefore, to deal with these problems, a web-based consumer complaint information system was created with system modeling using the Unifed Modeling Language (UML) and using the PHP programming language and MySQL as a database, so that it can overcome the problem of consumer complaints at PT. Sahabat Waskita Teknik more effectively and efficiently, bringing significant benefits to companies and consumers.